A line in space: Pricing, location, and market power in agricultural product markets - Marten Graubner; Klaus Salhofer; Christoph Tribl (Annual Review of Resource Economics, 2021)
Agricultural economists have a long history of emphasizing and analyzing the spatial dimension of agricultural and food markets. Despite a rich body of literature and important contributions to agricultural and spatial economics, one aspect is frequently disregarded: the oligopsonistic nature of agricultural markets due to spatial competition of neighboring buyers of farm products. This review presents the theoretical foundations of spatial pricing, competition, and location in terms of buyer power and discusses concepts that are relevant for agricultural markets. By providing a comprehensive overview of prior work, we highlight the multifaceted areas of applications to agricultural markets. Additionally, we discuss future research avenues for and challenges of the analysis of spatial competition in agricultural economics.
Keywords: L13; Q13; R32; 330; agricultural markets; spatial competition; buyer market power; spatial price discrimination; spatial differentiation